KAJIAN PENILAIAN KETANGGUHAN KOTA BANDUNG TERHADAP PANDEMI COVID-19 DENGAN PENDEKATAN BAYESIAN NETWORK - Audrina
Urban areas are the center of human’s activities and life. They were predicted more than half of human population lives in cities. However, cities are exceptionally vulnerable to pandemic like COVID-19, this is caused by the high intense human activities and density and the lack of sanitation and other basic infrastructure, especially in developing countries. This study aims to examine Bandung city’s probability to be resilient to COVID-19 with Bayesian Network. This study examines two resilient city functions, those are recovery and transformation functions, and five city qualities, those are resourcefulness, adaptation, inclusivity, redundancy, and robustness. This research used 28 selected indicators from rigorous literature study and expert prior knowledge. This research found that the probability for Bandung to be resilient from pandemic is 66% with 63% probability to recover and 65% probability to transform. This indicates that Bandung’s probability to be resilient can be categorized to moderate. Other than that, the probability of Bandung to recover and transform is about the same and can also be categorized as moderate. Therefore, it can conclude that Bandung still has to improve its’ resilience to pandemic. Next, the probability of Bandung to be inclusive is 87%, which is the highest among other qualities, followed by redundancy (74,45%). Meanwhile, the probability to adapt, be robust, and be resourceful are 70,06%, 68,79%, and 61,49%. This study concludes that the ability to be inclusive and redundant need to be maintained, especially the free COVID-19 vaccine, help mechanism to those vulnerable to domestic violance, BPJS to people, the existence of emergency facilities, and financial help to combat COVID-19 economic impact. Meanwhile, the ability to adapt, be robust, and be resourceful need to be improved by giving socialization to people about the importance of social distancing measures and vaccination, providing green spaces, basic infrastructure, health facilities, and COVID-19 vaccines.